Cancer pain : assessment and management - Bruera, Eduardo; Portenoy, Russell K. (Cambridge University Press, 2010)
Drs Eduardo D. Bruera and Russell K. Portenoy have completely revised and updated the widely respected Cancer Pain: Assessment and Management for the second edition of this unanimously praised book. This is a comprehensive, clinically oriented review of all aspects of the complex and multidimensional problem of cancer pain. The unique characteristics of cancer pain, including pathophysiology, clinical assessment, diagnosis, and pharmacological and nonpharmacological management are all discussed here in detail. Internationally recognized leaders in cancer pain research have contributed to many new chapters, including neuraxial analgesia, hospice and institution-based palliative care programs, bone pain, and cancer pain and palliative care in the developing world. Cancer Pain continues to be a scholarly but accessible text that is an essential resource for physicians, nurses, and medical students who treat suffering from cancer pain.